2017
DOI: 10.1016/j.pscychresns.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Resting state functional connectivity in primary insomnia, generalized anxiety disorder and controls

Abstract: Sleep abnormalities are extremely common in anxiety disorders and may contribute to their development and persistence. Their shared pathophysiological mechanisms could thus serve as biomarkers or targets for novel therapeutics. Individuals with Primary Insomnia were age- and sex-matched to controls and to persons with Generalized Anxiety Disorder. All underwent fMRI resting-state scans at 3-T. In Primary Insomnia and controls, sleep was recorded for 2 weeks using diaries and actigraphy. All participants comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 87 publications
1
41
0
Order By: Relevance
“…That is, more not less coupling between amygdala and sgACC was predicted by worse sleep when controlling for anxiety and depression symptoms. Findings are generally in line with a sleep deprivation resting-state study that reported increased FC between centromedial amygdala and rostral ACC in healthy individuals relative to rested wakefulness ( 65 ) and evidence of increased amygdala-rostral ACC FC in insomnia disorder when compared to generalized anxiety disorder ( 47 ). Notably, primate and effective connectivity studies indicate the amygdala has direct connections to sgACC ( 66 , 67 ), a region implicated in the modulation of emotional behavior ( 68 ) and known to be dysfunctional in IPs [e.g., depression; ( 69 )].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…That is, more not less coupling between amygdala and sgACC was predicted by worse sleep when controlling for anxiety and depression symptoms. Findings are generally in line with a sleep deprivation resting-state study that reported increased FC between centromedial amygdala and rostral ACC in healthy individuals relative to rested wakefulness ( 65 ) and evidence of increased amygdala-rostral ACC FC in insomnia disorder when compared to generalized anxiety disorder ( 47 ). Notably, primate and effective connectivity studies indicate the amygdala has direct connections to sgACC ( 66 , 67 ), a region implicated in the modulation of emotional behavior ( 68 ) and known to be dysfunctional in IPs [e.g., depression; ( 69 )].…”
Section: Discussionsupporting
confidence: 86%
“…For example, individuals with insomnia disorder (without concurrent psychiatric illness) exhibit altered rsFC between amygdala and the inferior frontal gyrus, subcortical structures (e.g., caudate, thalamus), temporal, parietal, and occipital regions relative to healthy controls ( 46 ). Also, limited research comparing insomnia disorder to an IP reported relatively more amygdala-rostral anterior cingulate cortex (ACC) rsFC in primary insomnia compared to generalized anxiety disorder ( 47 ). Though findings suggest a compensatory response in insomnia, both groups exhibited less amygdala-rostral ACC coupling than good sleepers signifying diminished top-down control of emotion regulation in these disorders ( 47 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies observed disruptions in FC within the DMN and in regions associated with executive function ( Li et al, 2014 , Nie et al, 2015 ), sensorimotor functions, and limbic regions ( Chen et al, 2014 , Killgore et al, 2013 , Huang et al, 2012 ), supporting previous physiological and emotional arousal findings associated with insomnia patients. A recent study found the resting-state FC between the amygdala and rostral anterior cingulate cortex to be intermediate in patients with primary insomnia compared to those with generalized anxiety disorder and controls, indicating that the emotional circuit is disrupted by insomnia ( Pace-Schott et al, 2017 ). Intrinsic resting-state activity, identified by brain entropy or regional homogeneity analyses, has also been introduced as a variable in insomnia studies, resulting in consistent evidence for hyperarousal in related structures such as the hippocampus, DMN, basal ganglia (BG) ( Zhou et al, 2016 ), and temporal cortex ( Dai et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resting‐state fMRI studies of insomnia disorder have highlighted the importance of the salience network in hyperarousal and affective symptoms (Khazaie et al., ). Specifically, researches revealed decreased functional connectivity between the amygdala and insula, striatum, thalamus, and bilateral ACC, and increased functional connectivity between the amygdala and premotor cortex, sensorimotor cortex in patients with primary insomnia, suggesting a potential neurological mechanism for dysfunction of emotional control and affective disorder in insomniacs (Huang et al., ; Pace‐Schott et al., ). Findings from another study showed that activation of the insula within the salience network was increased in insomniacs, which could be indicative of subthreshold anxiety, worry, and rumination (Chen, Chang, Glover, & Gotlib, ).…”
Section: Introductionmentioning
confidence: 99%